Analysis of Workload and Needs of Education Personnel Using the Total Quality Management (TQM) Method (Study at the Faculty of Engineering, Universitas Brawijaya) - Syaifuddin Syaifuddin (Wacana Journal of Social and Humanity Studies, 2019)
Being a superior, world class and active in developing the nation through the tri dharma process of higher education is UB's hope to improve service, transparency and accountability so as to create campus life with academic nuances which will eventually bring UB towards entrepreneurial university, (UB 2008 Governance Pattern ) The writing of this thesis aims to find out, identify and analyze the Workload and Needs of Educational Personnel Using the Total Quality Management Method (Study at the Faculty of Engineering, Universitas Brawijaya) by analyzing the data using Miles and Hubermen theory using descriptive qualitative research methods. The results of the study show that the workload of government institutions, especially also in the diving university environment, is still not considered enough so that the problems that arise in terms of providing services are often only associated with low work motivation and lack of work incentives. certain periods and no work appears in other periods. Therefore a step is needed to find out the workload for each position and the lowest work unit through workload analysis. With the analysis of workload, it will be known that the volume of work charged to a service unit and planning of human resource needs, including interpreting strategic policies in the future, especially for organizations in higher education so that they are in line with what has been defined in Resource Management Human College.